Advantages and Disadvantages of Health Care Accreditation Models - Andrew J. Wilson; Andrew J. Wilson; Farid Gharibi; Andrew J. Wilson; Jafar S. Tabrizi; Farid Gharibi; Jafar S. Tabrizi; Farid Gharibi; Jafar S. Tabrizi (Tabriz University of Medical Sciences, 2011)
Background: This systematic review seeks to define the general advantages and disadvantagesof accreditation programs to assist in choosing the most appropriate approach.Method: Systematic search of SID, Ovid Medline & PubMed databases was conducted by thekeywords of accreditation, hospital, medical practice, clinic, accreditation models, health careand Persian meanings. From 2379 initial articles, 83 articles met the full inclusion criteria.From initial analysis, 23 attributes were identified which appeared to define advantages anddisadvantages of different accreditation approaches and the available systems were comparedon these.Results: Six systems were identified in the international literature including the JCAHO fromUSA, the Canadian program of CCHSA, and the accreditation programs of UK, Australia,New Zealand and France. The main distinguishing attributes among them were: qualityimprovement, patient and staff safety, improving health services integration, public's confidence,effectiveness and efficiency of health services, innovation, influence global standards,information management, breadth of activity, history, effective relationship with stakeholders,agreement with AGIL attributes and independence from government.Conclusion: Based on 23 attributes of comprehensive accreditation systems we have definedfrom a systematic review, the JCAHO accreditation program of USA and then CCHSA ofCanada offered the most comprehensive systems with the least disadvantages. Other programssuch as the ACHS of Australia, ANAES of France, QHNZ of New Zealand and UK accreditationprograms were fairly comparable according to these criteria. However the decision forany country or health system should be based on an assessment weighing up their specificobjectives and needs.